Religiusitas dan Kematangan Beragama dalam Membantu Menghadapi Quarter-Life Crisis Bagi Kalangan Generasi Milenial - Sinta, Dewi; Rahmat, Munawar; Anwar, Saepul; Nurhuda, Abid; bin Engku Ab Rahman, Engku Shahrulerizal (UIR Press, 2024)
In this dynamic and digital era, millennials are often faced with challenging psychological challenges, especially the Quarter-Life Crisis. This study aims to analyze the contribution of religiosity and maturity in helping to deal with the Quarter-Life Crisis in the millennial generation. This research method uses a qualitative approach with a literature study method. Data collection is done by literature study, then data analysis using the content analysis method. The results showed that religiosity and religious maturity can help millennials in dealing with the Quarter-Life Crisis. The form of contribution is in the form of providing a moral foundation, inner strength, peace of mind, positive attitude, and self-acceptance, as well as improving psychological well-being. Individuals with high levels of religiosity and religious maturity tend to be better able to overcome Quarter-Life Crisis because they have more ability to control their emotions. These findings provide insight into the potential role of religious values in providing mental resilience for the millennial generation in facing the challenges of early adult life transition. The practical implications of this research include the need for the development of coaching programs that integrate religious aspects to help individuals manage their journey to adulthood.